The relationship between teachers' perception of the justice of organizational behavior and the level of commitment to organizational citizenship - Al-Shayea, Ali Saleh (IJRDO- Journal of Educational Research, 2016)
The present study aimed to identify the level of Qassim secondary teachers’awareness of organizational justice, and to identify their level of organizational citizenshipbehavior. The study also aimed to explore the nature of the relationship between teachers’perception of organizational justice and organizational citizenship behavior in Qassimsecondary schools, as well as any statistically significant relationships between teachers’perception of organizational justice, organizational citizenship behavior, and demographicvariables including sex and type of qualification. The study adopted a descriptive researchmethodology, drawing on the descriptive survey approach. The sample of the study consistedof 863 secondary teachers in Qassim educational region. The study utilized a tool that wasdeveloped by Niehoff and Moorman (1993) to measure organizational justice. The tool alsoutilized the work of Podsakoff et al. (1990) to measure organizational citizenship behavior. The study found that teachers’ perceptions of organizational justice were average,while their level of organizational citizenship behavior was high. There was a positivecorrelation between organizational justice and organizational citizenship behavior.Statistically significant differences were found in the perception of organizational justice dueto gender, while there were no differences due to experience and qualification. There were also no statistically significant differences in organizational citizenship behavior attributed tothe study variables